Continuous-wave fiber optical parametric amplifiers and oscillators - Lim, Lien Tze (2015)
Fiber optical parametric amplifier (FOPA) is an optical amplifier that operates based on an optical nonlinear phenomenon known as four-wave mixing (FWM). Parametric amplification takes place when a forward-propagating pump light and a signal light are injected into a gain medium of highly nonlinear fiber (HNLF). This fiber medium of choice has its nonlinearity enhanced by about a factor of 10 than conventional silica fiber, which could easily lead to the onset of nonlinear effects such as FWM, stimulated Raman scattering (SRS) and stimulated Brillouin scattering (SBS) when a high continuous-wave (CW) pump power is supplied into a long interaction length of gain fiber. The formation of parametric gain spectrum is dependent on the chromatic dispersion characteristics of the fiber as well, whereby the phase-matching condition has to be met through the detuning between the pump and zero dispersion wavelength (ZDW) of the fiber in achieving uniformity and wide bandwidth over 100 nm at any arbitrary wavelength. Several advantages reported on FOPA have brought to its discovery in various important functions such as large gain amplification, optical oscillation, optical sampling, transparent wavelength conversion and pulse generation. Previous investigation has shown that it is possible to transform a fiber optical parametric oscillator (FOPO) into a tunable radiation source that is capable of accessing wavelength regimes beyond the reach of conventional lasers. The nonlinear process of SRS on parametric amplification was found to be a useful mechanism in creating a broadband laser source since SRS allows the generation of new frequency at 100 nm away from the pump. The presented work in relation to wavelength conversion under SRS effect has proven to be successful through the achievement of tunable S-band idlers from a lasing signal at long oscillation wavelengths (where SRS is dominant) in an anomalously pumped FBG-formed linear cavity FOPO. On the other hand, by using similar configuration with cascaded oscillators, the generation of broadband multi-wavelength (MW) lasers through the degeneration of FWM was also reported to span from 1436 nm to 1704 nm at initial power of 450 mW (26.5 dBm). There is a need to control the gain competition between SRS and parametric process via the fiber Bragg grating (FBG) output reflectivity to achieve balance oscillation in this setup. Compared to previous Raman-assisted ring cavity FOPOs that operated under high pump power ranging from 3 W (35 dBm) to 5 W (37 dBm), the linear cavity FOPOs reported in this thesis have shown to perform well under low pump power of less than 1 W (30 dBm) to produce broadband laser at large pump-signal separation of over 100 nm. Moreover, further effort was made towards a single-frequency FOPO in a ring cavity configuration. In this demonstration, the single longitudinal mode (SLM) operation is realized using a 5 m fiber loop mirror (FLM) to increase the cavity mode spacing and a 35 cm long of un-pumped erbium-doped fiber (EDF) as the saturable absorber (SA) to select a single longitudinal mode in the cavity. As an outcome, an SLM laser with narrow linewidth of about 300 kHz (short term) has successfully measured at pump power of 1.188 W (30.75 dBm). Such achievement has indicated a significant improvement in the field since the first demonstration of SLM-FOPO did not specify nor reveal the performance of its SLM laser linewidth spectrally through measurement.